Molecular characterization of HEK293 cells as emerging versatile cell factories. (October 2021) - Pulix, Michela; Lukashchuk, Vera; Smith, Daniel C; Dickson, Alan J
Graphical abstract: Highlights: Manufacture of biopharmaceuticals, virus-like particles and viral vectors. System biology, 'omics, cellular phenotype and cell engineering. Cell line development, culture and bioprocess environment optimization. Abstract : HEK293 cell lines are used for the production of recombinant proteins, virus-like particles and viral vectors. Recent work has generated molecular (systems level) characterisation of HEK293 variants that has enabled re-engineering of the cells towards enhanced use for manufacture-scale production of recombinant biopharmaceuticals (assessment of 'safe harbours' for gene insertion, engineering of new variants for stable, amplifiable expression). In parallel, there have been notable advances in the bioprocessing conditions (suspension adaptation, development of defined serum-free media) that offer the potential for large-scale manufacture, a feature especially important in the drive to produce viral vectors at large-scale and at commercially viable costs for gene therapy. The combination of cell-based and bioprocess-based modification of existing HEK293 cell processes, frequently informed by understandings transferred from developments with Chinese hamster ovary cell lines, seems destined to place the HEK293 cell systems firmly as a critical platform for production of future biologically based therapeutics.